1989
DOI: 10.1161/01.res.65.5.1350
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic activity in a mathematical model of the vagally driven sinoatrial node.

Abstract: Phase-locking behavior and irregular dynamics were studied in a mathematical model of the sinus node driven with repetitive vagal input. The central region of the sinus node was simulated as a 15 x 15 array of resistively coupled pacemakers with each cell randomly assigned one of 10 intrinsic cycle lengths (range 290-390 msec). Coupling of the pacemakers resulted in their mutual entrainment to a common frequency and the emergence of a dominant pacemaker region. Repetitive acetylcholine (ACh; vagal) pulses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…While we have as yet no firm evidence of chaotic behavior in our simulations, there are several other modeling studies on spatially-extended electrophysiological systems showing apparently chaotic behavior, [56][57][58]61,90,92,108,[129][130][131] sometimes as the result of a period-doubling cascade. It is also quite possible that the spiral-or scroll-wave breakup seen in modeling work [56][57][58][59][60][61]113,132 might be an example of ''extensive chaos,'' 133 perhaps corresponding to ventricular fibrillation.…”
Section: Higher-order Period-doubled Rhythmsmentioning
confidence: 63%
See 1 more Smart Citation
“…While we have as yet no firm evidence of chaotic behavior in our simulations, there are several other modeling studies on spatially-extended electrophysiological systems showing apparently chaotic behavior, [56][57][58]61,90,92,108,[129][130][131] sometimes as the result of a period-doubling cascade. It is also quite possible that the spiral-or scroll-wave breakup seen in modeling work [56][57][58][59][60][61]113,132 might be an example of ''extensive chaos,'' 133 perhaps corresponding to ventricular fibrillation.…”
Section: Higher-order Period-doubled Rhythmsmentioning
confidence: 63%
“…The existence of period-2 and period-4 rhythms in ischemia, together with the experimental 42,45-47,88,109 and modeling 97,108,128,129 evidence for the period-doubling route to chaotic dynamics in cardiac tissue, leads very naturally to consideration of the possibility that the close temporal association of ventricular fibrillation with alternans might be an indication that ventricular fibrillation is a chaotic phenomenon somehow arising out of a cascade of period-doubling bifurcations. 9,32,37,38,52,53,111 Our results in the larger sheet ͑4 cmϫ4 cm, with a 2 cmϫ2 cm ischemic area͒ and the corresponding strand might be taken as providing some support for this hypothesis, in that we see the sequence ͕period-1→period-2→period-4→period-8→¯͖.…”
Section: Higher-order Period-doubled Rhythmsmentioning
confidence: 99%
“…In this regard, our system proposes a natural extension to a two-dimensional system (with both diffusions on the potential and on the recovery variable). This relates to physiological experiments made in cardiodynamics (Chialvo & Jalife 1987;Michaels et al 1989) in which a central nucleus of pacemaker is vagally driven. Our interpretation in terms of propagating bursting oscillations seems novel.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, this complex optimization tends to exhibit chaotic properties [34,35]. Because entropy is a measure of unpredictability and thus quantifies these chaotic properties, it can be concluded that a reduced HRV entropy reflects an impairment of the heart rate regulation.…”
Section: Discussionmentioning
confidence: 99%